(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Hypertension is one of the non-communicable diseases with high prevalence in the elderly group. The number of elderly in Indonesia in 2023 aged 60 years and over is 26,137,615 people (80%) who receive health services. So the role of cadres is to carry out promotive and preventive prevention. The study aims to see the age of the elderly, gender, the role of cadres and attitudes. The study used a correlation design with a cross-sectional approach connecting the role of cadres with the attitudes of the elderly. The number of samples used was 110 elderly people with hypertension in the Sempor 1 Health Center area. Data collection was carried out when the elderly attended the integrated service center and previously asked for approval from the health center, then the researchers looked for elderly hypertension. Next, the elderly were given an explanation about the research and agreed. Elderly hypertension was collected and given questions related to the role of cadres and attitudes. After being filled in and analyzed using chi-square. The results were the majority aged 60-69 years (early elderly) there were 54 people (491%), female gender as many as 77 people (70%). The role of the cadres was very good, there were 53 people (48.2%), their attitude was very good, there were 69 people (62.7%), and the results of the relationship with the Palue p-value = 0.992 were not related. This is influenced by many factors in the elderly, such as family support, elderly knowledge, trust and culture of the elderly towards formal health workers. Keywords: role of cadres, attitude of the elderly, hypertension